Historia i współczesność zapisane w języku. Pedagogiczne wędrówki po świecie związków frazeologicznych - Kuszak, Kinga (Kultura-Społeczeństwo-Edukacja, 2014)
The article attempts to search for continuity between the past and the present inscribed in the language, using selected idioms as examples. The author presents idioms as a linguistic “transmitter” of culture reflecting the experiences of its users. The paper concludes with a few reflections on the role of language education and creating the linguistic awareness of the young generation. The author highlights the need to combine the knowledge of the history of traditional idioms and the knowledge of using new idioms created for advertising and media purposes to shape the attitudes and language activity of young people.